2005
DOI: 10.2337/diacare.28.6.1390
|View full text |Cite
|
Sign up to set email alerts
|

Caffeinated Coffee, Decaffeinated Coffee, and Caffeine in Relation to Plasma C-Peptide Levels, a Marker of Insulin Secretion, in U.S. Women

Abstract: OBJECTIVE -Coffee consumption is associated with reduced risk of type 2 diabetes, but the mechanism is not clearly understood. Elevated C-peptide, as a marker of insulin secretion, has been linked to insulin-resistant type 2 diabetes. In this study, we examined consumption of caffeinated and decaffeinated coffee and total caffeine in relation to concentrations of plasma C-peptide.RESEARCH DESIGN AND METHODS -Plasma C-peptide concentrations were measured in a cross-sectional setting among 2,112 healthy women fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
109
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 35 publications
12
109
1
5
Order By: Relevance
“…These findings suggest that components of coffee other than caffeine contribute to the observed inverse association between coffee intake and uric acid levels. These findings closely agree with a recent study that found that both caffeinated and decaffeinated coffee were inversely associated with C peptide levels (a marker of endogenous insulin levels), but tea intake and total caffeine intake after adjusting for coffee intake were not (7). Because there is a strong positive relationship between serum insulin resistance and hyperuricemia (23)(24)(25)(26)(27) and insulin reduces the renal excretion of urate (25,28,29), decreased insulin resistance and insulin levels associated with coffee consumption may lead to lower uric acid levels.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These findings suggest that components of coffee other than caffeine contribute to the observed inverse association between coffee intake and uric acid levels. These findings closely agree with a recent study that found that both caffeinated and decaffeinated coffee were inversely associated with C peptide levels (a marker of endogenous insulin levels), but tea intake and total caffeine intake after adjusting for coffee intake were not (7). Because there is a strong positive relationship between serum insulin resistance and hyperuricemia (23)(24)(25)(26)(27) and insulin reduces the renal excretion of urate (25,28,29), decreased insulin resistance and insulin levels associated with coffee consumption may lead to lower uric acid levels.…”
supporting
confidence: 92%
“…Coffee and tea consumption may affect serum uric acid levels via various mechanisms including influence on insulin resistance (2)(3)(4)(5)(6)(7)(8)(9), but few data are available. Only 1 cross-sectional study investigated the link between these beverages and serum uric acid level based on 2,240 Japanese men and found a significant inverse association between coffee consumption and serum uric acid levels but no association with tea consumption (10).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, however, beneficial effects of coffee on glycaemic markers have been found and positive associations between coffee consumption and insulin sensitivity have been reported (Agardh et al, 2004;Arnlov et al, 2004;van Dam et al, 2004). Furthermore, coffee consumption of both caffeinated and decaffeinated coffee was associated with a decrease in C-peptide levels in women, indicating that chronic coffee consumption reduces insulin secretion (Wu et al, 2005). In our study, unfortunately, no information on insulin sensitivity or fasting glucose levels was available.…”
Section: Discussioncontrasting
confidence: 45%
“…This technique has been used for predictors such as alcohol consumption, 16 coffee consumption, 17 physical activity 18 and blood pressure. 19,20 We used the average BMI at visits 1, 2 and 3.…”
Section: Survival Analysesmentioning
confidence: 99%